Internationalization of Higher Education in China: Modern Trends - S. S. Donetskaya; Yan Zhan (Высшее образование в России)
The article analyzes the processes of internationalization of higher education in China at the beginning of the 21st century. Based on data from the Ministry of Education of China, legislation and publications that are publicly available on the Chinese Internet, it is shown how the number of students visiting China, their preferences in choosing universities and educational programs changed from 2000 to 2016. Information on government activities to support international students is provided.The internationalization of higher education plays an important role in the foreign-policy activities of modern China. Foreign students teaching and expanding of Chinese language teaching in foreign countries can be considered as the “soft power” of influence of Chinese national culture. Such actions from the point of view of the Chinese government should contribute to the formation of an attractive image of China, reduce the level of external threats, increase stability and economic prosperity of the country. Therefore, the government aims to attract as many foreign students as possible, especially from neighboring countries, and spends a lot of money on these purposes. The policy of internationalization of education has achieved significant results over the past 15 years. Today, students from all over the world obtain higher educationin China. The number of foreign students increased in 2016 compared to 2000 by 8.4 times, reaching almost 450 thousand people. The possibilities for foreign students to choose profession and university have expanded. Now they come to China not only to learn Chinese, but also to obtain qualifications in engineering, economics, management and Western medicine.